2013
DOI: 10.12669/pjms.296.3302
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of high sensitivity C-reactive protein with presence and severity of coronary artery disease

Abstract: Objective: Inflammation plays a key role in the pathogenesis of atherosclerosis. This study aimed to assess the relationship of serum inflammatory marker high sensitivity C Reactive protein (hsCRP), with the presence and severity of angiographically evaluated coronary artery disease (CAD). Methods: This study was conducted at departments of physiology and cardiology, College of Medicine & King Khalid University Hospital, King Saud University, Riyadh from August 2009 to March 2012. Eighty seven patients (57 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
3
24
0
1
Order By: Relevance
“…Unsurprisingly, we observed that IL-6 level positively correlates with other inflammatory parameters hsCRP and WBC, which is consistent with the results of other studies [19]. The levels of IL-6 [1,15,37] and hsCRP [38,39] could help predict the angiographic severity of CAD. It is well-known that these inflammatory markers have been linked to coronary events.…”
Section: Discussionsupporting
confidence: 91%
“…Unsurprisingly, we observed that IL-6 level positively correlates with other inflammatory parameters hsCRP and WBC, which is consistent with the results of other studies [19]. The levels of IL-6 [1,15,37] and hsCRP [38,39] could help predict the angiographic severity of CAD. It is well-known that these inflammatory markers have been linked to coronary events.…”
Section: Discussionsupporting
confidence: 91%
“…In this study we revealed statistically a significant difference in the level of hsCRP between patients with normal coronary arteries compared to those having angiographically atherosclerotic coronary artery lesions. A finding that was supported by earlier studies [10]. Here we detected as well a significant difference in the level of hsCRP between patients with single, two vessels and three vessels diseases, a finding which was comparable with other studies which detected higher hsCRP among patients with more severe coronary artery lesions, [11,7].…”
Section: Discussionsupporting
confidence: 93%
“…These data are also not consistent with data from other authors. Saudi patients with stable chronic CAD had higher hs-CRP levels compared to healthy individuals 27. Khan et al found that patients with chronic stable angina had elevated levels of hs-CRP 28…”
Section: Discussionmentioning
confidence: 99%